Antiproliferative activity of quercus infector/A galls extracts towards helaand caov-3 cancer cells and its apoptosis inducing activity on selected cancer cell lines - Chow Cheah, Yen (Universiti Sains Malaysia, 2009)
Quercus infectoria is an oak tree available in Asia Minor include Greece and Iran. The project is conducted to evaluate the antiproliferative activity of Quercus infectoria Olivier galls' extracts in vitro. Three extracts from aqueous crude extract by soaking and soxhlet method, one extract from ethanol crude extract by soaking method and one extract from methanol extract by soaking method were used. All the five crude extracts were used to treat HeLa and Caov-3 cancer cells line to screen for their antiproliferative activity. All the extracts shown to have ICso less than 100 Jlg/ml. Among them, the highest antiproliferative activity ofiC50 2.82 Jlg/ml was shown by the ethanol crude extract treated HeLa cancer cell lines. HeLa cells (most potent cell lines) was then treaed with ethanol crude extract for 24,48 and 72 hours and stain with dye Hoescht stain 33258 stain to demonstrate the morphological changes occur in cell and nuclear membrane as a result of apoptosis. In conclusion, Quercus infectoria galls' extracts contain potentially active compounds that act as anticancer agent.